Evaluation of potential gaseous emissions of asphalt rubber bituminous mixtures. Proposal of a new laboratory test procedure. (15th June 2016) - Zanetti, Maria Chiara; Santagata, Ezio; Fiore, Silvia; Ruffino, Barbara; Dalmazzo, Davide; Lanotte, Michele
Highlights: A new laboratory test was proposed for the generation of gaseous emissions from asphalt rubber bituminous mixtures. Gaseous emission of bituminous mixtures were sampled in the laboratory and at construction sites. Laboratory analyses focused on concentrations of potentially hazardous compounds. Experimental data were evaluated in the framework of a risk assessment model. The laboratory procedure in most cases yielded conservative values of risk parameters. Abstract: When deviating from standard paving solutions, it is necessary to verify that the use of supplementary components or the adoption of different processing conditions do not lead for construction workers to an increase of the risk associated to fume exposure. In the specific case of bituminous materials containing crumb rubber from end-of-life tyres, such an issue was addressed in an investigation in which a new laboratory test procedure for the evaluation of the composition and of the potential hazardous effects of gaseous emissions released during paving operations was developed and validated. Experimental activities were carried out by considering six different asphalt rubber mixtures, the emissions of which were sampled both in the field and in the laboratory. Subsequent analyses were performed by evaluating concentrations of volatile organic compounds and polycyclic aromatic hydrocarbons and by calculating corresponding toxic and carcinogenic risk parameters by means of adequate models. Effects of material-specific and site-specific factors were clearly distinguished and in most cases it was observed that analyses derived from laboratory-generated emissions led to a conservative estimate of risk. In general terms it was therefore concluded that the proposed procedure may be extremely valuable for the assessment of the true emission potential of bituminous mixtures containing crumb rubber and that in the future it may be employed as an evaluation tool during the mix design and field monitoring phases.